One Plus One Equals Three: The Synergy Between GenAI and Writing Centers in ESL Writing Development - Maphoto, Kgabo (Studies in Learning and Teaching, 2025)
This article examined the intersection of Generative Artificial Intelligence (GenAI), writing centers, and English as a Second Language (ESL) student support. It posed the central research question: ‘How can writing centers effectively integrate GenAI to support ESL student writers? The novelty of this research lies in its conceptual exploration of integrating GenAI into writing centers within a South African distance education (DE) context. The article addressed how this synergy can provide targeted, responsive, and culturally sensitive writing support designed for linguistically diverse students. The article conducted a comprehensive literature review and thematic synthesis, reviewing 35 scholarly sources to explore the theoretical and practical implications grounded in Sociocultural Theory (SCT). A conceptual design was employed to investigate the integration of GenAI in writing centers and its potential to support ESL students’ academic writing development. Results indicate that GenAI tools act as cognitive mediators, providing scaffolded support that enhances writing fluency, grammatical accuracy, and learner autonomy, particularly beneficial for DE students who often face isolation and limited access to human tutors. However, concerns such as over-reliance on GenAI tools, epistemological bias, and digital inequities highlight the need for human-mediated guidance and ethical integration. The article concluded that despite existing challenges, GenAI holds transformative potential as a complementary tool to enhance writing instruction. It advances inclusivity, self-regulated learning, and academic success among ESL students in multilingual and digitally constrained contexts.